Gradient pore composite solid electrolyte, and preparation method and application thereof
Patent Information
- Application Number
- CN202611216069.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-09-11
AI Technical Summary
[0004]然而,LATP在全固态电池中的应用仍面临诸多技术瓶颈
[0043]本发明提供了一种梯度孔复合固态电解质的制备方法,该方法采用不同浆料铺设在模具表面后,经加压、冷冻干燥后,得到包括大孔层、中间层和小孔层等具有梯度孔道分布的多孔坯体,进一步采用脉冲电流直接通过粉末颗粒,利用颗粒间等离子体放电产生瞬时高温形成多孔陶瓷片。更进一步,所述多孔陶瓷片采用预聚液进行原位填充后,能够完全进入多孔陶瓷片的孔隙中,固化,得到复合固态电解质。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery technology, specifically relating to a gradient pore composite solid electrolyte, its preparation method, and its application. Background Technology
[0002] In modern society, batteries have become a crucial power source for numerous devices, including smartphones, laptops, electric vehicles, and renewable energy grids. With the ever-increasing demand for portable electronics and electric vehicles, the need for high-performance, long-life, and highly safe batteries is becoming increasingly urgent. Advances in battery technology not only contribute to sustainable energy but also reduce dependence on fossil fuels, profoundly impacting people's lifestyles and work habits. However, lithium-ion batteries still face challenges related to safety and further improvements in energy density; therefore, strengthening research into battery technology is imperative.
[0003] Oxide inorganic solid electrolytes possess high ionic conductivity, providing a stable and efficient transport medium for ion flow between the anode and cathode in batteries. Simultaneously, solid electrolytes effectively suppress side reactions between the electrodes and the electrolyte, preventing lithium dendrite formation and contributing to improved overall battery energy density. For example, lithium aluminum titanium phosphate (LATP) exhibits advantages such as high ionic conductivity, good chemical stability, and low reactivity with lithium metal anodes, demonstrating significant potential in driving energy storage development and building safer, more efficient, and environmentally friendly batteries.
[0004] However, the application of LATP in all-solid-state batteries still faces many technical bottlenecks. Firstly, LATP is a NaSICON-type solid electrolyte with a sodium-ion conductor structure, belonging to the cubic crystal system with space group Fd-3m. Its ionic conductivity is relatively low, approximately 10-3. -3 ~10 -4 The low S / cm severely limits its practical application in all-solid-state batteries. Secondly, LATP possesses inherent mechanical rigidity, resulting in poor film density after deposition, and the presence of porosity further reduces its ionic conductivity. Furthermore, the high solid-solid interface resistance between the oxide solid electrolyte and the positive and negative electrode materials further restricts its performance in all-solid-state batteries. Of particular note is the high grain boundary resistance of LATP polycrystalline ceramic sheets, which is one of the main factors limiting its bulk conductivity.
[0005] Therefore, how to effectively reduce the grain boundary resistance and interfacial resistance of LATP ceramic sheets, and improve their film density and ionic conductivity, has become a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0006] In view of this, the purpose of this invention is to provide a composite solid electrolyte, its preparation method, and its application. This composite solid electrolyte material possesses characteristics such as high ionic conductivity and stable material structure, and its application in all-solid-state batteries can improve battery energy density, charge / discharge rate, and safety stability.
[0007] To achieve this objective, the present invention adopts the following technical solution:
[0008] In a first aspect, the present invention provides a method for preparing a gradient pore composite solid electrolyte, comprising the following steps:
[0009] S1: Provide macroporous layer slurry, intermediate layer slurry and microporous layer slurry. After the three slurries are laid on the surface of the mold in sequence, pressure is applied and freeze-drying is performed to obtain a porous preform.
[0010] The macroporous layer slurry includes LATP and NaCl whiskers, the intermediate layer slurry includes LATP, lithium-containing substances and glucose, and the microporous layer slurry includes LATP, nano-NaCl and functional additives, wherein the functional additives include any one or more of lithium fluoride, lithium difluorooxalate borate, lithium difluorophosphate or lithium nitride.
[0011] The porous preform includes a macroporous layer, an intermediate layer, and a microporous layer; the macroporous layer has a pore size of 3~5 μm, the intermediate layer has a pore size of 1~2 μm, and the microporous layer has a pore size of 0.5~1 μm.
[0012] S2: Apply a pulsed current to the porous preform and then remove NaCl to obtain a porous ceramic sheet;
[0013] S3: The prepolymer liquid is filled into the porous ceramic sheet in situ, cured under ultraviolet light, and then annealed to obtain the composite solid electrolyte.
[0014] Preferably, the prepolymer liquid comprises macromonomers, vinyl monomers, lithium-ion-containing polymerizable monomers, and photoinitiators.
[0015] Preferably, the macromonomer includes polyethylene glycol diacrylate and / or polyethylene glycol dimethacrylate.
[0016] Preferably, the vinyl monomer includes any one or more of acrylamide, methyl methacrylate, or acrylonitrile.
[0017] Preferably, the lithium-ion-containing polymerizable monomer includes lithium acrylate and / or lithium bis(fluorosulfonyl)imide.
[0018] Preferably, the photoinitiator includes any one or more of photoinitiator 1173 (2-hydroxy-2-methyl-1-phenyl-1-propanone), photoinitiator TPO (2,4,6-trimethylbenzoyl-diphenylphosphine oxide), and photoinitiator 819 (diacylphosphine oxide).
[0019] Preferably, the prepolymer liquid comprises, by mass, 4-6 parts of macromolecular monomer and 3-5 parts of vinyl monomer.
[0020] Preferably, the mass of the lithium-ion-containing polymerizable monomer is 10-20% of the total mass of the macromonomer and vinyl monomer.
[0021] Preferably, the mass of the photoinitiator is 1 to 3% of the total mass of the macromolecular monomer, vinyl monomer, and lithium-ion-containing polymerizable monomer.
[0022] Preferably, in the macroporous slurry, the mass of the NaCl whiskers is 30-40% of LATP.
[0023] Preferably, the NaCl whiskers have an aspect ratio of 5 to 10:1 and a diameter of 3 to 5 μm.
[0024] Preferably, the thickness of the macroporous slurry layer is 20~30 μm.
[0025] Preferably, the lithium-containing material includes any one or more of lithium phosphate, lithium difluorooxalate borate, lithium difluorophosphate, or lithium nitride, and the particle size of the lithium-containing material is 0.2~0.5 μm.
[0026] Preferably, in the intermediate layer slurry, the mass of lithium-containing substances is 10-30% of LATP, and the mass of glucose is 20-30% of LATP.
[0027] Preferably, the glucose has a particle size of 1~2 μm.
[0028] Preferably, the thickness of the intermediate layer slurry is 15~20 μm.
[0029] Preferably, in the microporous slurry, the mass of nano-NaCl is 10-20% of LATP, and the mass of functional additives is 3-5% of LATP.
[0030] Preferably, the particle size of the nano-NaCl is 0.5~1 μm.
[0031] Preferably, the particle size of the functional additive is 0.2~0.5 μm.
[0032] Preferably, the thickness of the pore layer slurry is 10~15 μm.
[0033] Preferably, the pressurization pressure is 20~50 MPa.
[0034] Preferably, the freeze-drying temperature is -20 to -40°C and the time is 24 to 48 hours.
[0035] Preferably, the pulse current has a current range of 10~30 kA and a frequency of 10 Hz~30 kHz.
[0036] Preferably, the porosity of the porous ceramic sheet is 45-55%.
[0037] Preferably, the UV curing parameters are: 365~385 nm, 500~800 mJ / cm². 2 .
[0038] Preferably, the annealing temperature is 130~150℃ and the time is 1~3 h.
[0039] Preferably, the thickness of the composite solid electrolyte is 50~80 μm.
[0040] Secondly, the present invention provides a gradient pore composite solid electrolyte prepared by the above preparation method.
[0041] Thirdly, the present invention provides an all-solid-state battery, which includes the gradient pore composite solid electrolyte involved in the above-mentioned technical solution.
[0042] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0043] This invention provides a method for preparing a gradient-pore composite solid electrolyte. The method involves laying different slurries on the surface of a mold, followed by pressurization and freeze-drying to obtain a porous preform with a gradient pore distribution, including macropore layers, intermediate layers, and micropore layers. Further, a pulsed current is directly passed through the powder particles, utilizing inter-particle plasma discharge to generate instantaneous high temperatures to form porous ceramic sheets. Furthermore, the porous ceramic sheets are in-situ filled with a prepolymer solution, which completely penetrates the pores of the porous ceramic sheets and solidifies to obtain the composite solid electrolyte.
[0044] In this invention, when the gradient pore composite solid electrolyte is applied, the macropore layer is close to the positive electrode interface, which can load more polymer solid electrolyte, thereby significantly reducing the internal resistance of the solid-solid reaction interface of the oxide solid electrolyte. The intermediate layer can improve the lithium ion transport rate, and a fast ion conductor is added therein. The micropore layer faces the negative electrode, which can effectively prevent lithium dendrite formation and improve safety.
[0045] Furthermore, the polymer formed after the prepolymer solution solidifies can completely seal the pores of the porous ceramic sheet. Simultaneously, coating both sides of the porous ceramic sheet with the polymer not only reduces the porosity of the LATP ceramic sheet but also increases its ionic conductivity. Additionally, the LATP within the polymer reduces its crystallinity, improving the Li ion diffusion rate and its ability to withstand high voltages. Moreover, the polymer itself is in direct contact with the positive and negative electrodes, reducing the solid-solid interface effect between LATP and the electrodes.
[0046] In summary, the composite solid electrolyte material designed based on this invention has characteristics such as high ionic conductivity and stable material structure, and can be applied to all-solid-state batteries to improve battery performance and stability, such as improving battery energy density, charge-discharge rate, and safety stability. Attached Figure Description
[0047] Figure 1 This is a SEM image of the macroporous layer of the porous ceramic sheet in Example 1;
[0048] Figure 2 This is a SEM image of the middle layer of the porous ceramic sheet in Example 1;
[0049] Figure 3 This is a SEM image of the pore layer of the porous ceramic sheet in Example 1. Detailed Implementation
[0050] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0051] To address the issue of high grain boundary resistance in polycrystalline ceramic sheets in existing all-solid-state batteries, this invention provides a composite solid electrolyte. LATP is fabricated into porous ceramic sheets using a template method, and a polymer solid electrolyte is used to completely fill the pores of the porous ceramic sheets, reducing porosity and generating denser ceramic sheets. Simultaneously, a polymer solid electrolyte is generated around the ceramic sheets, reducing the solid-solid reaction interface between the LATP ceramic sheets and the positive and negative electrodes, further enhancing its application in all-solid-state batteries.
[0052] Specifically, the technical solution of the present invention will be described from the following aspects.
[0053] In a first aspect, the present invention provides a method for preparing a gradient pore composite solid electrolyte, comprising the following steps:
[0054] S1: Provide macroporous layer slurry, intermediate layer slurry and microporous layer slurry. After the three slurries are laid on the surface of the mold in sequence, pressure is applied and freeze-drying is performed to obtain a porous preform.
[0055] The macroporous layer slurry includes LATP and NaCl whiskers, the intermediate layer slurry includes LATP, lithium-containing substances and glucose, and the microporous layer slurry includes LATP, nano-NaCl and functional additives, wherein the functional additives include any one or more of lithium fluoride, lithium difluorooxalate borate, lithium difluorophosphate or lithium nitride.
[0056] The porous preform includes a macroporous layer, an intermediate layer, and a microporous layer; the macroporous layer has a pore size of 3~5 μm, the intermediate layer has a pore size of 1~2 μm, and the microporous layer has a pore size of 0.5~1 μm.
[0057] S2: Apply a pulsed current to the porous preform and then remove NaCl to obtain a porous ceramic sheet;
[0058] S3: The prepolymer liquid is filled into the porous ceramic sheet in situ, cured under ultraviolet light, and then annealed to obtain the composite solid electrolyte.
[0059] According to the present invention, LATP is first prepared.
[0060] In this invention, the general formula of LATP is Li 1+x Al x Ti 2-x (PO4)3, 0 < x ≤ 0.9, such as 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 or 0.9, etc.
[0061] In some embodiments of the present invention, lithium source, aluminum source, titanium source and phosphorus source are placed in a high-energy ball mill according to the stoichiometric ratio of the general formula of LATP, using ethanol solution as solvent, with a solid content of 10% to 30%, a ball-to-material mass ratio of 2:1 to 5:1, a rotation speed of 300 to 500 rpm, and a ball milling time of 3 to 5 h. The above slurry is dried at 100 to 120°C for 4 to 8 h, and then placed in a muffle furnace and heated to 900 to 1000°C at a heating rate of 2 to 3°C / min, and held for 3 to 10 h to obtain LATP material.
[0062] Then, according to the present invention, a macroporous layer slurry, an intermediate layer slurry and a microporous layer slurry are provided. The three slurries are sequentially laid on the surface of the mold and then pressurized. The pressurized mold is then freeze-dried to obtain a porous preform.
[0063] The macroporous layer slurry comprises LATP and NaCl whiskers. The NaCl whiskers have an aspect ratio of 5 to 10:1, such as 5:1, 6:1, 7:1, 8:1, 9:1, or 10:1; and a diameter of 3 to 5 μm, such as 3 μm, 3.5 μm, 4 μm, 4.5 μm, or 5 μm.
[0064] In some embodiments of the present invention, the mass of NaCl whiskers in the macroporous layer slurry is 30-40% of LATP, such as 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, or 40%.
[0065] In some embodiments of the present invention, LATP and NaCl whiskers are preferably mixed in a certain proportion and then ultrasonically dispersed using deionized water as the dispersion medium for 5-60 min, preferably 10-30 min. The thickness of the macroporous slurry is 20-30 μm, such as 20 μm, 21 μm, 22 μm, 23 μm, 24 μm, 25 μm, 26 μm, 27 μm, 28 μm, 29 μm, or 30 μm.
[0066] In this invention, the intermediate layer slurry comprises LATP, a lithium-containing substance, and glucose. The lithium-containing substance comprises any one or more of lithium phosphate, lithium difluorooxalate borate, lithium difluorophosphate, or lithium nitride, and the particle size of the lithium-containing substance is 0.2~0.5 μm, such as 0.2 μm, 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, or 0.5 μm, etc.; the glucose particle size is 1~2 μm, such as 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, or 2 μm, etc.
[0067] In some embodiments of the present invention, the mass of lithium-containing material in the intermediate layer slurry is 10-30% of LATP, such as 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, or 30%; the mass of glucose is 20-30% of LATP, such as 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, or 30%.
[0068] In some embodiments of the present invention, LATP, lithium-containing substances, and glucose are mixed in a certain proportion and dispersed using an alcohol reagent, preferably ethanol. The thickness of the intermediate layer slurry is 15-20 μm, such as 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, or 20 μm.
[0069] In this invention, the microporous layer slurry comprises LATP, nano-NaCl, and functional additives. The nano-NaCl has a particle size of 0.5–1 μm, such as 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, or 1 μm. The functional additives comprise any one or more of lithium fluoride, lithium difluorooxalate borate, lithium difluorophosphate, or lithium nitride. The functional additives have a particle size of 0.2–0.5 μm, such as 0.2 μm, 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, or 0.5 μm.
[0070] In some embodiments of the present invention, the mass of nano-NaCl in the microporous layer slurry is 10-20% of LATP, such as 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%; the mass of the functional additive is 3-5% of LATP, such as 3%, 3.5%, 4%, 4.5% or 5% etc.
[0071] In some embodiments of the present invention, LATP, nano-NaCl, and functional additives are mixed in a certain proportion and then dispersed using an alcohol reagent, preferably isopropanol. The thickness of the pore layer slurry is 10-15 μm, such as 10 μm, 10.5 μm, 11 μm, 11.5 μm, 12 μm, 12.5 μm, 13 μm, 13.5 μm, 14 μm, 14.5 μm, or 15 μm.
[0072] In this invention, after obtaining the aforementioned macroporous layer slurry, intermediate layer slurry, and microporous layer slurry, the three slurries are sequentially laid on the surface of a mold and then pressurized. The pressurized mold is then freeze-dried, utilizing ice crystal growth to form directional interconnected pores, thus obtaining a porous preform. The pressurization pressure is 20~50 MPa, preferably 30~40 MPa; the freeze-drying temperature is -20~-40℃, preferably -25~-30℃; and the time is 24~48 h, preferably 30~36 h.
[0073] Then, according to the present invention, a pulsed current is applied to the porous preform to remove NaCl, thereby obtaining a porous ceramic sheet.
[0074] This invention uses pulsed current to directly pass through powder particles, utilizing inter-particle plasma discharge to generate instantaneous high temperatures to form porous ceramic sheets.
[0075] In some embodiments of the present invention, the pulse current has a current range of 10~30 kA, preferably 10~20 kA; a frequency of 10 Hz~30 kHz, preferably 10 Hz~20 kHz; and a pressure fluctuation of less than 0.5 MPa is controlled to prevent gaps from forming in the sintered porous ceramic sheet.
[0076] The above-mentioned NaCl removal method involves boiling in deionized water for 1-4 hours, preferably 2-3 hours. In this invention, NaCl removal is to prevent lithium-sodium ion exchange between sodium ions and the solid electrolyte.
[0077] Tests showed that the porosity of the porous ceramic sheet prepared above was 45-55%, preferably 48-50%.
[0078] To clarify, the macroporous layer slurry specifically selects a combination of LATP and NaCl whiskers to facilitate the formation of the macroporous layer and to facilitate the subsequent removal of substances that form the pores; the intermediate layer slurry includes LATP, lithium-containing substances, and glucose to facilitate the formation of the mesoporous layer, and the lithium-containing substances improve the ionic conductivity; the microporous layer slurry includes LATP, nano-NaCl, and functional additives to facilitate the formation of the microporous layer, forming the SEI film required for the negative electrode, and improving the stability and performance of the negative electrode.
[0079] Then, according to the present invention, the prepolymer liquid is filled into the porous ceramic sheet in situ, cured under ultraviolet light, and then annealed to obtain the composite solid electrolyte.
[0080] In this invention, the prepolymer liquid comprises macromonomers, vinyl monomers, lithium-ion-containing polymerizable monomers, and photoinitiators.
[0081] Wherein, the macromonomer includes polyethylene glycol diacrylate and / or polyethylene glycol dimethacrylate; the vinyl monomer includes any one or more of acrylamide, methyl methacrylate, or acrylonitrile; the lithium-ion-containing polymerizable monomer includes lithium acrylate and / or lithium bis(fluorosulfonyl)imide; the photoinitiator includes any one or more of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, or diacylphosphine oxide.
[0082] In some embodiments of the present invention, the prepolymer liquid comprises, by weight, 4 to 6 parts of macromonomer, such as 4 parts, 4.5 parts, 5 parts, 5.5 parts, or 6 parts; and 3 to 5 parts of vinyl monomer, such as 3 parts, 3.5 parts, 4 parts, 4.5 parts, or 5 parts. Furthermore, the mass of the lithium-ion-containing polymerizable monomer is 10 to 20% of the total mass of the macromonomer and vinyl monomer, such as 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, or 20%; and the mass of the photoinitiator is 1 to 3% of the total mass of the macromonomer, vinyl monomer, and lithium-ion-containing polymerizable monomer, such as 1%, 1.5%, 2%, 2.5%, or 3%.
[0083] In some embodiments of the present invention, the parameters of the ultraviolet curing are: 365~385 nm, preferably 365~380 nm; 500~800 mJ / cm 2 Preferably, it is 500~700 mJ / cm 2 The annealing temperature is 130~150℃, preferably 130~140℃, and the time is 1~3 h, preferably 1~2 h.
[0084] In some embodiments of the present invention, the thickness of the composite solid electrolyte is 50~80 μm, such as 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm or 80 μm, etc.
[0085] In some embodiments of the present invention, after the macromonomer, vinyl monomer, lithium-ion-containing polymerizable monomer and photoinitiator are mixed evenly, the resulting prepolymer liquid is vacuum-injected into a porous ceramic sheet containing a gradient framework, UV curing is performed to form a covalent network, annealing is performed to promote the coordination of Li ions with carboxylate groups to form an ion network, and finally a composite solid electrolyte is formed.
[0086] The present invention also provides a composite solid electrolyte prepared by the above preparation method.
[0087] Furthermore, the present invention provides an all-solid-state battery, wherein the composite solid-state electrolyte involved in the above-mentioned technical solution is described above.
[0088] In the all-solid-state battery, the positive electrode can be selected from ternary materials or lithium iron phosphate materials, the negative electrode can be selected from graphite, silicon carbon, or lithium negative electrode, and the separator can be a conventional commercially available material.
[0089] Testing has shown that the composite solid electrolyte material provided by this invention has characteristics such as high ionic conductivity and stable material structure, and can be applied to all-solid-state batteries to improve battery performance and stability.
[0090] To further illustrate the present invention, the following embodiments provide a detailed description. Unless otherwise specified, all experimental materials used in the following embodiments of the present invention are commercially available products.
[0091] Example 1
[0092] 54.31 g of lithium carbonate, 20.40 g of alumina, 127.79 g of titanium dioxide, and 345.08 g of ammonium dihydrogen phosphate were weighed and placed in a high-energy ball mill. Ethanol solution was used as the solvent, the solid content was 10%, the ball-to-material mass ratio was 5:1, the rotation speed was 500 r / min, and the ball milling time was 5 h. The above slurry was dried at 120℃ for 8 h, and then placed in a muffle furnace and heated to 900℃ at a heating rate of 2℃ / min and held for 3 h to obtain LATP material.
[0093] Macroporous layer slurry: Weigh 0.5 g of LATP and 0.17 g of NaCl whiskers (aspect ratio 10:1, diameter 5 μm), place them in 3.35 g of deionized water, and ultrasonically disperse for 30 min. Intermediate layer slurry: Weigh 0.5 g of LATP, 0.075 g of lithium phosphate with a particle size of 0.2 μm, 0.14 g of glucose with a particle size of 2 μm, and disperse in 3.58 g of ethanol. Microporous layer slurry: Weigh 0.5 g of LATP, 0.025 g of lithium fluoride with a particle size of 0.2 μm, 0.1 g of NaCl with a particle size of 0.5 μm, and disperse in 3.13 g of isopropanol. Then, sequentially lay the three slurries onto a polytetrafluoroethylene mold. The macroporous layer has a thickness of 20 μm, the intermediate layer 15 μm, and the microporous layer 10 μm. The pore size of the macroporous layer is 5 μm, the intermediate layer 2 μm, and the microporous layer 0.5 μm. A pressure of 50 MPa was applied, and the mixture was freeze-dried at -40℃ for 24 h to form directional interconnected pores through ice crystal growth. Subsequently, a pulsed current was directly passed through the powder particles, and instantaneous high temperatures were generated by interparticle plasma discharge to form porous ceramic sheets (SEM images of the macropore layer, intermediate layer, and micropore layer of this porous ceramic sheet are shown below). Figures 1-3 As shown), the current is 10 kA, the frequency is 10 Hz, the pressure fluctuation is ≤0.5 MPa, and deionized water is boiled for 2 h to remove NaCl, finally forming a gradient skeleton product with a porosity of 50%.
[0094] Weigh out 1 g of polyethylene glycol diacrylate, 3 g of acrylamide, 1 g of lithium acrylate, and 0.05 g of photoinitiator. Mix them thoroughly and dissolve them in dimethyl sulfoxide to form a homogeneous mixture. Vacuum infuse the prepolymer solution into a gradient framework, then remove the solvent under vacuum in a vacuum oven and cure under ultraviolet light (365 nm, 500 mJ / cm). 2A covalent network is formed, which promotes the coordination of Li ions and carboxylate ions to form an ion network, resulting in a final composite electrolyte thickness of 50 μm.
[0095] Example 2
[0096] 54.31 g of lithium carbonate, 20.40 g of alumina, 127.79 g of titanium dioxide, and 345.08 g of ammonium dihydrogen phosphate were weighed and placed in a high-energy ball mill. Ethanol solution was used as the solvent, the solid content was 30%, the ball-to-material mass ratio was 5:1, the rotation speed was 500 r / min, and the ball milling time was 5 h. The above slurry was dried at 120℃ for 8 h, and then placed in a muffle furnace and heated to 900℃ at a heating rate of 2℃ / min and held for 3 h to obtain LATP material.
[0097] Macroporous layer slurry: Weigh 0.5 g of LATP and 0.17 g of NaCl whiskers (aspect ratio 5:1, diameter 3 μm), place in deionized water, and ultrasonically disperse for 30 min. Intermediate layer slurry: Weigh 0.5 g of LATP, 0.075 g of lithium phosphate with a particle size of 0.2 μm, and 0.14 g of glucose with a particle size of 1 μm, and disperse in ethanol. Microporous layer slurry: Weigh 0.5 g of LATP, 0.025 g of lithium fluoride with a particle size of 0.2 μm, and 0.1 g of NaCl with a particle size of 1 μm, and disperse in isopropanol. The three slurries are then sequentially laid on a polytetrafluoroethylene mold, with a macroporous layer thickness of 20 μm, an intermediate layer thickness of 15 μm, and a microporous layer thickness of 10 μm. The pore size of the macroporous layer is 3 μm, the intermediate layer has a pore size of 1 μm, and the microporous layer has a pore size of 1 μm. A pressure of 50 MPa was applied, and the mixture was freeze-dried at -40℃ for 24 h to form directional interconnected pores through ice crystal growth. Subsequently, a pulsed current was directly passed through the powder particles, and instantaneous high temperature was generated by interparticle plasma discharge to form porous ceramic sheets. The current was 10 kA, the frequency was 10 Hz, and the pressure fluctuation was ≤0.5 MPa. NaCl was removed by boiling in deionized water for 2 h, and finally a gradient framework product with a porosity of 45% was formed.
[0098] Weigh out 1 g of polyethylene glycol diacrylate, 3 g of acrylamide, 1 g of lithium acrylate, and 0.05 g of photoinitiator. Mix them thoroughly and dissolve them in dimethyl sulfoxide to form a homogeneous mixture. Vacuum infuse the prepolymer solution into a gradient framework, then remove the solvent under vacuum in a vacuum oven and cure under ultraviolet light (365 nm, 500 mJ / cm). 2 A covalent network is formed, which promotes the coordination of Li ions and carboxylate ions to form an ion network, resulting in a final composite electrolyte thickness of 50 μm.
[0099] Example 3
[0100] 54.31 g of lithium carbonate, 20.40 g of alumina, 127.79 g of titanium dioxide, and 345.08 g of ammonium dihydrogen phosphate were weighed and placed in a high-energy ball mill. Ethanol solution was used as the solvent, the solid content was 10%, the ball-to-material mass ratio was 5:1, the rotation speed was 500 r / min, and the ball milling time was 3 h. The slurry was dried at 100℃ for 8 h, and then placed in a muffle furnace and heated to 900℃ at a heating rate of 2℃ / min and held for 3 h to obtain LATP material.
[0101] Macroporous layer slurry: Weigh 0.5 g of LATP and 0.17 g of NaCl whiskers (aspect ratio 10:1, diameter 5 μm), place in deionized water, and ultrasonically disperse for 30 min. Intermediate layer slurry: Weigh 0.5 g of LATP, 0.075 g of lithium phosphate with a particle size of 0.2 μm, and 0.14 g of glucose with a particle size of 2 μm, and disperse in ethanol. Microporous layer slurry: Weigh 0.5 g of LATP, 0.025 g of lithium fluoride with a particle size of 0.2 μm, and 0.1 g of NaCl with a particle size of 1 μm, and disperse in isopropanol. Then, sequentially lay the three slurries onto a polytetrafluoroethylene mold. The macroporous layer has a thickness of 20 μm, the intermediate layer 15 μm, and the microporous layer 10 μm. The pore size of the macroporous layer is 5 μm, the intermediate layer 2 μm, and the microporous layer 1 μm. A pressure of 50 MPa was applied, and the mixture was freeze-dried at -40℃ for 24 h to form directional interconnected pores through ice crystal growth. Subsequently, a pulsed current was directly passed through the powder particles, and instantaneous high temperatures were generated by interparticle plasma discharge to form porous ceramic sheets. The current range was 10 kA, the frequency was 10 Hz, and the pressure fluctuation was ≤0.5 MPa. NaCl was removed by boiling in deionized water for 2 h, and finally a gradient framework product with a porosity of 55% was formed.
[0102] Weigh out 1 g of polyethylene glycol diacrylate, 3 g of acrylamide, 1 g of lithium acrylate, and 0.05 g of photoinitiator. Mix them thoroughly and dissolve them in dimethyl sulfoxide to form a homogeneous mixture. Vacuum infuse the prepolymer solution into a gradient framework, then remove the solvent under vacuum in a vacuum oven and cure under ultraviolet light (365 nm, 500 mJ / cm). 2 A covalent network is formed, which promotes the coordination of Li ions and carboxylate ions to form an ion network, resulting in a final composite electrolyte thickness of 50 μm.
[0103] Example 4
[0104] 54.31 g of lithium carbonate, 20.40 g of alumina, 127.79 g of titanium dioxide, and 345.08 g of ammonium dihydrogen phosphate were weighed and placed in a high-energy ball mill. Ethanol solution was used as the solvent, the solid content was 10%, the ball-to-material mass ratio was 5:1, the rotation speed was 500 r / min, and the ball milling time was 5 h. The slurry was dried at 120℃ for 8 h, and then placed in a muffle furnace and heated to 1000℃ at a heating rate of 2℃ / min and held for 3 h to obtain LATP material.
[0105] Macroporous layer slurry: Weigh 0.5 g of LATP and 0.17 g of NaCl whiskers (aspect ratio 10:1, diameter 5 μm), place in deionized water, and ultrasonically disperse for 30 min. Intermediate layer slurry: Weigh 0.5 g of LATP, 0.075 g of lithium phosphate with a particle size of 0.2 μm, and 0.14 g of glucose with a particle size of 2 μm, and disperse in ethanol. Microporous layer slurry: Weigh 0.5 g of LATP, 0.025 g of lithium fluoride with a particle size of 0.2 μm, and 0.1 g of NaCl with a particle size of 0.5 μm, and disperse in isopropanol. The three slurries are then sequentially laid on a polytetrafluoroethylene mold, with a macroporous layer thickness of 20 μm, an intermediate layer thickness of 15 μm, and a microporous layer thickness of 10 μm. The macroporous layer has a pore size of 5 μm, the intermediate layer has a pore size of 2 μm, and the microporous layer has a pore size of 0.5 μm. A pressure of 50 MPa was applied, and the mixture was freeze-dried at -40℃ for 24 h to form directional interconnected pores through ice crystal growth. Subsequently, a pulsed current was directly passed through the powder particles, and instantaneous high temperature was generated by interparticle plasma discharge to form porous ceramic sheets. The current was 10 kA, the frequency was 10 Hz, and the pressure fluctuation was ≤0.5 MPa. NaCl was removed by boiling in deionized water for 2 h, and finally a gradient framework product with a porosity of 50% was formed.
[0106] Weigh out 1 g of polyethylene glycol diacrylate, 3 g of acrylamide, 1 g of lithium acrylate, and 0.05 g of photoinitiator. Mix them thoroughly and dissolve them in dimethyl sulfoxide to form a homogeneous mixture. Vacuum infuse the prepolymer solution into a gradient framework, then remove the solvent under vacuum in a vacuum oven and cure under ultraviolet light (385 nm, 800 mJ / cm). 2 A covalent network is formed, which promotes the coordination of Li ions and carboxylate ions to form an ion network, resulting in a final composite electrolyte thickness of 50 μm.
[0107] Example 5
[0108] 54.31 g of lithium carbonate, 20.40 g of alumina, 127.79 g of titanium dioxide, and 345.08 g of ammonium dihydrogen phosphate were weighed and placed in a high-energy ball mill. Ethanol solution was used as the solvent, the solid content was 10%, the ball-to-material mass ratio was 5:1, the rotation speed was 500 r / min, and the ball milling time was 5 h. The above slurry was dried at 120℃ for 8 h, and then placed in a muffle furnace and heated to 1000℃ at a heating rate of 2℃ / min and held for 10 h to obtain LATP material.
[0109] Macroporous layer slurry: Weigh 0.5 g of LATP and 0.17 g of NaCl whiskers (aspect ratio 10:1, diameter 5 μm), place in deionized water, and ultrasonically disperse for 30 min. Intermediate layer slurry: Weigh 0.5 g of LATP, 0.075 g of lithium phosphate with a particle size of 0.2 μm, and 0.14 g of glucose with a particle size of 2 μm, and disperse in ethanol. Microporous layer slurry: Weigh 0.5 g of LATP, 0.025 g of lithium fluoride with a particle size of 0.2 μm, and 0.1 g of NaCl with a particle size of 0.5 μm, and disperse in isopropanol. The three slurries are then sequentially laid on a polytetrafluoroethylene mold, with a macroporous layer thickness of 20 μm, an intermediate layer thickness of 15 μm, and a microporous layer thickness of 10 μm. The macroporous layer has a pore size of 5 μm, the intermediate layer has a pore size of 2 μm, and the microporous layer has a pore size of 0.5 μm. A pressure of 50 MPa was applied, and the mixture was freeze-dried at -40℃ for 24 h to form directional interconnected pores through ice crystal growth. Subsequently, a pulsed current was directly passed through the powder particles, and instantaneous high temperature was generated by interparticle plasma discharge to form porous ceramic sheets. The current was 30 kA, the frequency was 10 Hz, and the pressure fluctuation was ≤0.5 MPa. NaCl was removed by boiling in deionized water for 4 h, and finally a gradient framework product with a porosity of 50% was formed.
[0110] Weigh out 1 g of polyethylene glycol diacrylate, 3 g of acrylamide, 1 g of lithium acrylate, and 0.05 g of photoinitiator. Mix them thoroughly and dissolve them in dimethyl sulfoxide to form a homogeneous mixture. Vacuum infuse the prepolymer solution into a gradient framework, then remove the solvent under vacuum in a vacuum oven and cure under ultraviolet light (365 nm, 500 mJ / cm). 2 A covalent network is formed, which promotes the coordination of Li ions and carboxylate ions to form an ion network, resulting in a final composite electrolyte thickness of 50 μm.
[0111] Example 6
[0112] 54.31 g of lithium carbonate, 20.40 g of alumina, 127.79 g of titanium dioxide, and 345.08 g of ammonium dihydrogen phosphate were weighed and placed in a high-energy ball mill. Ethanol solution was used as the solvent, the solid content was 10%, the ball-to-material mass ratio was 5:1, the rotation speed was 500 r / min, and the ball milling time was 5 h. The above slurry was dried at 120℃ for 8 h, and then placed in a muffle furnace and heated to 900℃ at a heating rate of 2℃ / min and held for 3 h to obtain LATP material.
[0113] Macroporous layer slurry: Weigh 0.5 g of LATP and 0.17 g of NaCl whiskers (aspect ratio 10:1, diameter 5 μm), place in deionized water, and ultrasonically disperse for 30 min. Intermediate layer slurry: Weigh 0.5 g of LATP, 0.075 g of lithium phosphate with a particle size of 0.2 μm, and 0.14 g of glucose with a particle size of 2 μm, and disperse in ethanol. Microporous layer slurry: Weigh 0.5 g of LATP, 0.025 g of lithium fluoride with a particle size of 0.2 μm, and 0.1 g of NaCl with a particle size of 0.5 μm, and disperse in isopropanol. The three slurries are then sequentially laid on a polytetrafluoroethylene mold, with a macroporous layer thickness of 30 μm, an intermediate layer thickness of 15 μm, and a microporous layer thickness of 10 μm. The macroporous layer has a pore size of 5 μm, the intermediate layer has a pore size of 2 μm, and the microporous layer has a pore size of 0.5 μm. A pressure of 50 MPa was applied, and the mixture was freeze-dried at -40℃ for 24 h to form directional interconnected pores through ice crystal growth. Subsequently, a pulsed current was directly passed through the powder particles, and instantaneous high temperature was generated by interparticle plasma discharge to form porous ceramic sheets. The current was 10 kA, the frequency was 30 kHz, and the pressure fluctuation was ≤0.5 MPa. NaCl was removed by boiling in deionized water for 2 h, and finally a gradient framework product with a porosity of 50% was formed.
[0114] Weigh out 1 g of polyethylene glycol diacrylate, 3 g of acrylamide, 1 g of lithium acrylate, and 0.05 g of photoinitiator. Mix them thoroughly and dissolve them in dimethyl sulfoxide to form a homogeneous mixture. Vacuum infuse the prepolymer solution into a gradient framework, then remove the solvent under vacuum in a vacuum oven and cure under ultraviolet light (365 nm, 500 mJ / cm). 2 A covalent network is formed, which promotes the coordination of Li ions and carboxylate ions to form an ion network, resulting in a final composite electrolyte thickness of 60 μm.
[0115] Example 7
[0116] 54.31 g of lithium carbonate, 20.40 g of alumina, 127.79 g of titanium dioxide, and 345.08 g of ammonium dihydrogen phosphate were weighed and placed in a high-energy ball mill. Ethanol solution was used as the solvent, the solid content was 10%, the ball-to-material mass ratio was 5:1, the rotation speed was 500 r / min, and the ball milling time was 5 h. The above slurry was dried at 120℃ for 8 h, and then placed in a muffle furnace and heated to 900℃ at a heating rate of 2℃ / min and held for 3 h to obtain LATP material.
[0117] Macroporous layer slurry: Weigh 0.5 g of LATP and 0.17 g of NaCl whiskers (aspect ratio 10:1, diameter 5 μm), place in deionized water, and ultrasonically disperse for 30 min. Intermediate layer slurry: Weigh 0.5 g of LATP, 0.075 g of lithium phosphate with a particle size of 0.2 μm, and 0.14 g of glucose with a particle size of 2 μm, and disperse in ethanol. Microporous layer slurry: Weigh 0.5 g of LATP, 0.025 g of lithium fluoride with a particle size of 0.2 μm, and 0.1 g of NaCl with a particle size of 0.5 μm, and disperse in isopropanol. Then, sequentially lay the three slurries onto a polytetrafluoroethylene mold. The macroporous layer has a thickness of 20 μm, the intermediate layer 20 μm, and the microporous layer 15 μm. The pore size of the macroporous layer is 5 μm, the intermediate layer 2 μm, and the microporous layer 0.5 μm. A pressure of 50 MPa was applied, and the mixture was freeze-dried at -40℃ for 24 h to form directional interconnected pores through ice crystal growth. Subsequently, a pulsed current was directly passed through the powder particles, and instantaneous high temperature was generated by interparticle plasma discharge to form porous ceramic sheets. The current was 10 kA, the frequency was 10 Hz, and the pressure fluctuation was ≤0.5 MPa. NaCl was removed by boiling in deionized water for 2 h, and finally a gradient framework product with a porosity of 50% was formed.
[0118] Weigh out 1 g of polyethylene glycol diacrylate, 3 g of acrylamide, 1 g of lithium acrylate, and 0.05 g of photoinitiator. Mix them thoroughly and dissolve them in dimethyl sulfoxide to form a homogeneous mixture. Vacuum infuse the prepolymer solution into a gradient framework, then remove the solvent under vacuum in a vacuum oven and cure under ultraviolet light (365 nm, 500 mJ / cm). 2 A covalent network is formed, which promotes the coordination of Li ions and carboxylate ions to form an ion network, resulting in a final composite electrolyte thickness of 60 μm.
[0119] Example 8
[0120] 54.31 g of lithium carbonate, 20.40 g of alumina, 127.79 g of titanium dioxide, and 345.08 g of ammonium dihydrogen phosphate were weighed and placed in a high-energy ball mill. Ethanol solution was used as the solvent, the solid content was 10%, the ball-to-material mass ratio was 5:1, the rotation speed was 500 r / min, and the ball milling time was 5 h. The above slurry was dried at 120℃ for 8 h, and then placed in a muffle furnace and heated to 900℃ at a heating rate of 2℃ / min and held for 3 h to obtain LATP material.
[0121] Macroporous layer slurry: Weigh 0.5 g of LATP and 0.17 g of NaCl whiskers (aspect ratio 10:1, diameter 5 μm), place in deionized water, and ultrasonically disperse for 30 min. Intermediate layer slurry: Weigh 0.5 g of LATP, 0.075 g of lithium phosphate with a particle size of 0.2 μm, and 0.14 g of glucose with a particle size of 2 μm, and disperse in ethanol. Microporous layer slurry: Weigh 0.5 g of LATP, 0.025 g of lithium fluoride with a particle size of 0.2 μm, and 0.1 g of NaCl with a particle size of 0.5 μm, and disperse in isopropanol. Then, sequentially lay the three slurries onto a polytetrafluoroethylene mold. The macroporous layer thickness is 20 μm, the intermediate layer is 15 μm, and the microporous layer is 15 μm. The pore size of the macroporous layer is 5 μm, the intermediate layer is 2 μm, and the microporous layer is 0.5 μm. A pressure of 20 MPa was applied, and the mixture was freeze-dried at -40℃ for 24 h to form directional interconnected pores through ice crystal growth. Subsequently, a pulsed current was directly passed through the powder particles, and instantaneous high temperatures were generated by interparticle plasma discharge to form porous ceramic sheets. The current range was 10 kA, the frequency was 10 Hz, and the pressure fluctuation was ≤0.5 MPa. NaCl was removed by boiling in deionized water for 1 h, finally forming a gradient framework product with a porosity of 50%.
[0122] Weigh out 1 g of polyethylene glycol diacrylate, 3 g of acrylamide, 1 g of lithium acrylate, and 0.05 g of photoinitiator. Mix them thoroughly and dissolve them in dimethyl sulfoxide to form a homogeneous mixture. Vacuum infuse the prepolymer solution into a gradient framework, then remove the solvent under vacuum in a vacuum oven and cure under ultraviolet light (365 nm, 500 mJ / cm). 2 A covalent network is formed, which promotes the coordination of Li ions and carboxylate ions to form an ion network, resulting in a final composite electrolyte thickness of 55 μm.
[0123] Example 9
[0124] 54.31 g of lithium carbonate, 20.40 g of alumina, 127.79 g of titanium dioxide, and 345.08 g of ammonium dihydrogen phosphate were weighed and placed in a high-energy ball mill. Ethanol solution was used as the solvent, the solid content was 10%, the ball-to-material mass ratio was 5:1, the rotation speed was 500 r / min, and the ball milling time was 5 h. The above slurry was dried at 120℃ for 8 h, and then placed in a muffle furnace and heated to 900℃ at a heating rate of 2℃ / min and held for 3 h to obtain LATP material.
[0125] Macroporous layer slurry: Weigh 0.5 g of LATP and 0.17 g of NaCl whiskers (aspect ratio 10:1, diameter 5 μm), place them in 3.35 g of deionized water, and ultrasonically disperse for 30 min. Intermediate layer slurry: Weigh 0.5 g of LATP, 0.075 g of lithium phosphate with a particle size of 0.2 μm, and 0.14 g of glucose with a particle size of 2 μm, and disperse in ethanol. Microporous layer slurry: Weigh 0.5 g of LATP, 0.025 g of lithium fluoride with a particle size of 0.2 μm, and 0.1 g of NaCl with a particle size of 0.5 μm, and disperse in isopropanol. Then, sequentially lay the three slurries onto a polytetrafluoroethylene mold. The macroporous layer has a thickness of 20 μm, the intermediate layer 15 μm, and the microporous layer 10 μm. The pore size of the macroporous layer is 5 μm, the intermediate layer 2 μm, and the microporous layer 0.5 μm. A pressure of 50 MPa was applied, and the mixture was freeze-dried at -40℃ for 24 h to form directional interconnected pores through ice crystal growth. Subsequently, a pulsed current was directly passed through the powder particles, and instantaneous high temperature was generated by interparticle plasma discharge to form porous ceramic sheets. The current range was 10 kA, the frequency was 10 Hz, and the pressure fluctuation was ≤0.5 MPa. NaCl was removed by boiling in deionized water for 2 h, and finally a gradient framework product with a porosity of 50% was formed.
[0126] Weigh out 1 g of polyethylene glycol diacrylate, 3 g of acrylamide, 1 g of lithium acrylate, and 0.05 g of photoinitiator. Mix them thoroughly and dissolve them in dimethyl sulfoxide to form a homogeneous mixture. Vacuum infuse the prepolymer solution into a gradient framework, then remove the solvent under vacuum in a vacuum oven and cure under ultraviolet light (365 nm, 500 mJ / cm). 2 A covalent network is formed, which promotes the coordination of Li ions and carboxylate ions to form an ion network, resulting in a final composite electrolyte thickness of 80 μm.
[0127] Example 10
[0128] 54.31 g of lithium carbonate, 20.40 g of alumina, 127.79 g of titanium dioxide, and 345.08 g of ammonium dihydrogen phosphate were weighed and placed in a high-energy ball mill. Ethanol solution was used as the solvent, the solid content was 30%, the ball-to-material mass ratio was 5:1, the rotation speed was 500 r / min, and the ball milling time was 5 h. The above slurry was dried at 120℃ for 8 h, and then placed in a muffle furnace and heated to 900℃ at a heating rate of 2℃ / min and held for 3 h to obtain LATP material.
[0129] Macroporous layer slurry: Weigh 0.5 g of LATP and 0.17 g of NaCl whiskers (aspect ratio 10:1, diameter 5 μm), place them in 3.35 g of deionized water, and ultrasonically disperse for 30 min. Intermediate layer slurry: Weigh 0.5 g of LATP, 0.075 g of lithium phosphate with a particle size of 0.2 μm, 0.14 g of glucose with a particle size of 2 μm, and disperse in 3.58 g of ethanol. Microporous layer slurry: Weigh 0.5 g of LATP, 0.025 g of lithium difluorooxalate borate with a particle size of 0.2 μm, 0.1 g of NaCl with a particle size of 0.5 μm, and disperse in 3.13 g of isopropanol. Subsequently, three layers of slurry were sequentially laid on a polytetrafluoroethylene mold: a macroporous layer with a thickness of 20 μm, an intermediate layer with a thickness of 15 μm, and a microporous layer with a thickness of 10 μm. The pore size of the macroporous layer was 5 μm, the intermediate layer had a pore size of 2 μm, and the microporous layer had a pore size of 0.5 μm. A pressure of 50 MPa was applied, and the mixture was freeze-dried at -40℃ for 24 h to form directional interconnected pores through ice crystal growth. Then, a pulsed current was directly passed through the powder particles, utilizing interparticle plasma discharge to generate instantaneous high temperatures and form porous ceramic sheets. The current was 10 kA, the frequency was 10 Hz, and the pressure fluctuation was ≤0.5 MPa. NaCl was removed by boiling in deionized water for 2 h, ultimately forming a gradient framework product with a porosity of 50%.
[0130] Weigh out 1 g of polyethylene glycol diacrylate, 3 g of acrylamide, 1 g of lithium acrylate, and 0.05 g of photoinitiator. Mix them thoroughly and dissolve them in dimethyl sulfoxide to form a homogeneous mixture. Vacuum infuse the prepolymer solution into a gradient framework, then remove the solvent under vacuum in a vacuum oven and cure under ultraviolet light (365 nm, 500 mJ / cm). 2 A covalent network is formed, which promotes the coordination of Li ions and carboxylate ions to form an ion network, resulting in a final composite electrolyte thickness of 50 μm.
[0131] Example 11
[0132] 54.31 g of lithium carbonate, 20.40 g of alumina, 127.79 g of titanium dioxide, and 345.08 g of ammonium dihydrogen phosphate were weighed and placed in a high-energy ball mill. Ethanol solution was used as the solvent, the solid content was 30%, the ball-to-material mass ratio was 5:1, the rotation speed was 500 r / min, and the ball milling time was 5 h. The above slurry was dried at 120℃ for 8 h, and then placed in a muffle furnace and heated to 900℃ at a heating rate of 2℃ / min and held for 3 h to obtain LATP material.
[0133] Macroporous layer slurry: Weigh 0.5 g of LATP and 0.17 g of NaCl whiskers (aspect ratio 10:1, diameter 5 μm), place them in 3.35 g of deionized water, and ultrasonically disperse for 30 min. Intermediate layer slurry: Weigh 0.5 g of LATP, 0.075 g of lithium phosphate with a particle size of 0.2 μm, 0.14 g of glucose with a particle size of 2 μm, and disperse in 3.58 g of ethanol. Microporous layer slurry: Weigh 0.5 g of LATP, 0.025 g of lithium difluorophosphate with a particle size of 0.2 μm, 0.1 g of NaCl with a particle size of 0.5 μm, and disperse in 3.13 g of isopropanol. Subsequently, three layers of slurry were sequentially laid on a polytetrafluoroethylene mold: a macroporous layer with a thickness of 20 μm, an intermediate layer with a thickness of 15 μm, and a microporous layer with a thickness of 10 μm. The pore diameter of the macroporous layer was 5 μm, the pore diameter of the intermediate layer was 2 μm, and the pore diameter of the microporous layer was 0.5 μm. A pressure of 50 MPa was applied, and the mixture was freeze-dried at -40℃ for 24 h to form directional interconnected pores through ice crystal growth. Then, a pulsed current was directly passed through the powder particles, utilizing interparticle plasma discharge to generate instantaneous high temperatures and form porous ceramic sheets. The current was 10 kA, the frequency was 10 Hz, and the pressure fluctuation was ≤0.5 MPa. NaCl was removed by boiling in deionized water for 2 h, ultimately forming a gradient framework product with a porosity of 50%.
[0134] Weigh out 1 g of polyethylene glycol diacrylate, 3 g of acrylamide, 1 g of lithium acrylate, and 0.05 g of photoinitiator. Mix them thoroughly and dissolve them in dimethyl sulfoxide to form a homogeneous mixture. Vacuum infuse the prepolymer solution into a gradient framework, then remove the solvent under vacuum in a vacuum oven and cure under ultraviolet light (365 nm, 500 mJ / cm). 2 A covalent network is formed, which promotes the coordination of Li ions and carboxylate ions to form an ion network, resulting in a final composite electrolyte thickness of 50 μm.
[0135] Example 12
[0136] 54.31 g of lithium carbonate, 20.40 g of alumina, 127.79 g of titanium dioxide, and 345.08 g of ammonium dihydrogen phosphate were weighed and placed in a high-energy ball mill. Ethanol solution was used as the solvent, the solid content was 30%, the ball-to-material mass ratio was 5:1, the rotation speed was 500 r / min, and the ball milling time was 5 h. The above slurry was dried at 120℃ for 8 h, and then placed in a muffle furnace and heated to 900℃ at a heating rate of 2℃ / min and held for 3 h to obtain LATP material.
[0137] Macroporous layer slurry: Weigh 0.5 g of LATP and 0.17 g of NaCl whiskers (aspect ratio 10:1, diameter 5 μm), place them in 3.35 g of deionized water, and ultrasonically disperse for 30 min. Intermediate layer slurry: Weigh 0.5 g of LATP, 0.075 g of lithium phosphate with a particle size of 0.2 μm, 0.14 g of glucose with a particle size of 2 μm, and disperse in 3.58 g of ethanol. Microporous layer slurry: Weigh 0.5 g of LATP, 0.025 g of lithium difluorophosphate with a particle size of 0.2 μm, 0.1 g of NaCl with a particle size of 0.5 μm, and disperse in 3.13 g of isopropanol. Subsequently, three layers of slurry were sequentially laid on a polytetrafluoroethylene mold: a macroporous layer with a thickness of 20 μm, an intermediate layer with a thickness of 15 μm, and a microporous layer with a thickness of 10 μm. The pore diameter of the macroporous layer was 5 μm, the pore diameter of the intermediate layer was 2 μm, and the pore diameter of the microporous layer was 0.5 μm. A pressure of 50 MPa was applied, and the mixture was freeze-dried at -40℃ for 24 h to form directional interconnected pores through ice crystal growth. Then, a pulsed current was directly passed through the powder particles, utilizing interparticle plasma discharge to generate instantaneous high temperatures and form porous ceramic sheets. The current was 10 kA, the frequency was 10 Hz, and the pressure fluctuation was ≤0.5 MPa. NaCl was removed by boiling in deionized water for 2 h, ultimately forming a gradient framework product with a porosity of 50%.
[0138] Weigh out 1 g of polyethylene glycol dimethacrylate, 3 g of methyl methacrylate, 1 g of lithium bis(fluorosulfonyl)imide, and 0.05 g of photoinitiator. Mix them thoroughly and dissolve them in dimethyl sulfoxide to form a homogeneous mixture. Vacuum pour the prepolymer solution into the gradient framework, then remove the solvent under vacuum in a vacuum oven and cure under ultraviolet light (365 nm, 500 mJ / cm). 2 A covalent network is formed, which promotes the coordination of Li ions and carboxylate ions to form an ion network, resulting in a final composite electrolyte thickness of 50 μm.
[0139] Example 13
[0140] 54.31 g of lithium carbonate, 20.40 g of alumina, 127.79 g of titanium dioxide, and 345.08 g of ammonium dihydrogen phosphate were weighed and placed in a high-energy ball mill. Ethanol solution was used as the solvent, the solid content was 30%, the ball-to-material mass ratio was 5:1, the rotation speed was 500 r / min, and the ball milling time was 5 h. The above slurry was dried at 120℃ for 8 h, and then placed in a muffle furnace and heated to 900℃ at a heating rate of 2℃ / min and held for 3 h to obtain LATP material.
[0141] Macroporous layer slurry: Weigh 0.5 g of LATP and 0.17 g of NaCl whiskers (aspect ratio 10:1, diameter 5 μm), place them in 3.35 g of deionized water, and ultrasonically disperse for 30 min. Intermediate layer slurry: Weigh 0.5 g of LATP, 0.075 g of lithium phosphate with a particle size of 0.2 μm, 0.14 g of glucose with a particle size of 2 μm, and disperse in 3.58 g of ethanol. Microporous layer slurry: Weigh 0.5 g of LATP, 0.025 g of lithium difluorophosphate with a particle size of 0.2 μm, 0.1 g of NaCl with a particle size of 0.5 μm, and disperse in 3.13 g of isopropanol. Subsequently, three layers of slurry were sequentially laid on a polytetrafluoroethylene mold: a macroporous layer with a thickness of 20 μm, an intermediate layer with a thickness of 15 μm, and a microporous layer with a thickness of 10 μm. The pore diameter of the macroporous layer was 5 μm, the pore diameter of the intermediate layer was 2 μm, and the pore diameter of the microporous layer was 0.5 μm. A pressure of 50 MPa was applied, and the mixture was freeze-dried at -40℃ for 24 h to form directional interconnected pores through ice crystal growth. Then, a pulsed current was directly passed through the powder particles, utilizing interparticle plasma discharge to generate instantaneous high temperatures and form porous ceramic sheets. The current was 10 kA, the frequency was 10 Hz, and the pressure fluctuation was ≤0.5 MPa. NaCl was removed by boiling in deionized water for 2 h, ultimately forming a gradient framework product with a porosity of 50%.
[0142] Weigh out 1 g of polyethylene glycol diacrylate, 3 g of acrylonitrile, 1 g of lithium bis(fluorosulfonyl)imide, and 0.05 g of photoinitiator. Mix them thoroughly and dissolve them in dimethyl sulfoxide to form a homogeneous mixture. Vacuum infuse the prepolymer solution into a gradient framework, then remove the solvent under vacuum in a vacuum oven and cure under ultraviolet light (365 nm, 500 mJ / cm). 2 A covalent network is formed, which promotes the coordination of Li ions and carboxylate ions to form an ion network, resulting in a final composite electrolyte thickness of 50 μm.
[0143] Comparative Example 1
[0144] 54.31 g of lithium carbonate, 20.40 g of alumina, 127.79 g of titanium dioxide, and 345.08 g of ammonium dihydrogen phosphate were weighed and placed in a high-energy ball mill. Ethanol solution was used as the solvent, the solid content was 10%, the ball-to-material mass ratio was 5:1, the rotation speed was 500 r / min, and the ball milling time was 5 h. The above slurry was dried at 120℃ for 8 h, and then placed in a muffle furnace and heated to 900℃ at a heating rate of 2℃ / min and held for 3 h to obtain LATP material.
[0145] Macroporous layer slurry: Weigh 0.5 g of LATP and 0.17 g of NaCl whiskers (aspect ratio 10:1, diameter 5 μm), place in deionized water, and ultrasonically disperse for 30 min. Intermediate layer slurry: Weigh 0.5 g of LATP, 0.075 g of lithium phosphate with a particle size of 0.2 μm, and 0.14 g of glucose with a particle size of 2 μm, disperse in ethanol. Microporous layer slurry: Weigh 0.5 g of LATP, 0.025 g of lithium fluoride with a particle size of 0.2 μm, and 0.1 g of NaCl with a particle size of 0.5 μm, disperse in isopropanol. The three slurries are then sequentially laid on a polytetrafluoroethylene mold, with a macroporous layer thickness of 20 μm, an intermediate layer thickness of 15 μm, and a microporous layer thickness of 10 μm. Apply a pressure of 50 MPa and freeze-dry at -40℃ for 24 h to form directional interconnected pores through ice crystal growth. Subsequently, a pulsed current is directly passed through the powder particles, and instantaneous high temperature is generated by interparticle plasma discharge to form porous ceramic sheets. The current range is 10 kA, the frequency is 10 Hz, and the pressure fluctuation is ≤0.5 MPa. NaCl is removed by boiling in deionized water for 2 h, and the final gradient framework product is used as a composite electrolyte.
[0146] Comparative Example 2
[0147] 54.31 g of lithium carbonate, 20.40 g of alumina, 127.79 g of titanium dioxide, and 345.08 g of ammonium dihydrogen phosphate were weighed and placed in a high-energy ball mill. Ethanol solution was used as the solvent, the solid content was 10%, the ball-to-material mass ratio was 5:1, the rotation speed was 500 r / min, and the ball milling time was 5 h. The above slurry was dried at 120℃ for 8 h, and then placed in a muffle furnace and heated to 900℃ at a heating rate of 2℃ / min and held for 3 h to obtain LATP material.
[0148] 1.5 g of LATP was weighed, subjected to a pressure of 50 MPa, and freeze-dried at -40℃ for 24 h. Subsequently, a pulsed current was directly passed through the powder particles, and a porous ceramic sheet was formed by instantaneous high temperature generated by interparticle plasma discharge. The current was 10 kA, the frequency was 10 Hz, and the pressure fluctuation was ≤0.5 MPa. NaCl was removed by boiling in deionized water for 2 h, and finally, an LATP product with a thickness of 45 μm was formed.
[0149] Weigh out 2 g of polyethylene glycol diacrylate, 6 g of acrylamide, 2 g of lithium acrylate, and 0.1 g of photoinitiator. Mix them thoroughly and dissolve them in dimethyl sulfoxide to form a homogeneous mixture. Vacuum pour the prepolymer solution into a gradient framework, then remove the solvent under vacuum in a vacuum oven and cure under ultraviolet light (365 nm, 500 mJ / cm). 2 A covalent network is formed, which promotes the coordination of Li ions and carboxylate ions to form an ion network, resulting in a final composite electrolyte thickness of 80 μm.
[0150] Performance testing
[0151] 1- Ionic conductivity test
[0152] The testing method is as follows: Take the ceramic sheet (as electrolyte) obtained in the above examples and comparative examples, and gently polish its surface using 1000-grit sandpaper moistened with alcohol in a cross-grit method to remove surface impurities and ensure that the thickness of the electrolyte is uniform in all positions. Measure the thickness L of the ceramic sheet using calipers, deposit a gold blocking electrode using an ion sputtering apparatus, and test the ionic conductivity of LATP using AC impedance spectroscopy, denoted as σ. Ionic conductivity: Spray gold onto both sides of the electrolyte, remove the gold powder around the edges with 1000-grit sandpaper, and then perform cyclic testing at 0.1~10 MHz in a 25℃ constant temperature chamber. The calculation formula is: σ=L / (Rb×S), where σ is the ionic conductivity (S / cm), L is the thickness of the electrolyte sheet (cm), Rb is the bulk resistance (Ω), and S is the electrode contact area (cm²). 2 The ionic conductivity can be obtained from the formula.
[0153] The test results are shown in Table 1:
[0154] Table 1
[0155]
[0156] As shown in Table 1, based on the ionic conductivity test data of Examples 1-13 and Comparative Examples 1-2, the solution provided by this invention exhibits higher ionic conductivity at room temperature (25°C). Specifically, the ionic conductivity of Examples 1-13 ranges from 0.77 mS / cm to 0.98 mS / cm, with the highest value reaching 0.98 mS / cm (Example 1) and the lowest value being 0.77 mS / cm (Example 12). In contrast, the ionic conductivity of Comparative Example 1 is only 0.56 mS / cm, and that of Comparative Example 2 is 0.69 mS / cm, both significantly lower than the lowest values of all examples. This indicates that, compared to the comparative examples, the technical solution of this invention can effectively improve the ion transport capacity of the electrolyte, thereby achieving superior electrochemical performance. Therefore, the electrolyte system described in this invention shows significant progress in ionic conductivity.
[0157] 2- Cycle retention test of all-solid-state batteries
[0158] The testing method is as follows: CR2032 coin cells are prepared using the ceramic sheets obtained in the above examples and comparative examples. The negative electrode is a lithium sheet, the positive electrode is a lithium iron phosphate system, and the electrolyte is a solid ceramic sheet.
[0159] The assembled button cells were subjected to constant current charge-discharge tests on the battery testing system, with a voltage range of 2.5~3.65 V and a rate of 0.05 C.
[0160] The test results are shown in Table 2:
[0161] Table 2
[0162]
[0163] As shown in Table 2, based on the cycle retention rate test results of Examples 1-13 and Comparative Examples 1-2 at a rate of 0.05C, the technical solution provided by this invention has a significant advantage in long-term cycle stability. Specifically, Examples 1-13 exhibit capacity retention rates between 92.78% and 96.21% after 100 cycles, between 88.45% and 92.04% after 200 cycles, and between 85.21% and 87.23% after 300 cycles, all demonstrating excellent and stable cycle performance. Among them, Example 1 maintains 87.23% capacity after 300 cycles, the highest value among all examples; even Example 12, with relatively lower cycle performance, still maintains 85.21% capacity after 300 cycles. In contrast, Comparative Example 1 showed retention rates of only 82.84%, 78.22%, and 74.91% after 100, 200, and 300 cycles, respectively, while Comparative Example 2 showed rates of only 89.11%, 84.93%, and 78.11%, respectively. These figures are significantly lower than the lowest retention rates achieved by all embodiments at the corresponding cycle counts. These data clearly demonstrate that, compared to the comparative examples, the present invention can more effectively maintain the stability of the electrode / electrolyte interface and significantly suppress capacity decay during long cycles, thereby giving the battery a superior cycle life. Therefore, the technical solution described in this invention has achieved unexpected progress in cycle performance.
[0164] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a gradient pore composite solid-state electrolyte, characterized by, Includes the following steps: S1: Provide macroporous layer slurry, intermediate layer slurry and microporous layer slurry. After the three slurries are laid on the surface of the mold in sequence, pressure is applied and freeze-drying is performed to obtain a porous preform. The macroporous layer slurry includes LATP and NaCl whiskers, the intermediate layer slurry includes LATP, lithium-containing substances and glucose, and the microporous layer slurry includes LATP, nano-NaCl and functional additives, wherein the functional additives include any one or more of lithium fluoride, lithium difluorooxalate borate, lithium difluorophosphate or lithium nitride. The porous preform includes a macroporous layer, an intermediate layer, and a microporous layer; the macroporous layer has a pore size of 3~5 μm, the intermediate layer has a pore size of 1~2 μm, and the microporous layer has a pore size of 0.5~1 μm. S2: Apply a pulsed current to the porous preform and then remove NaCl to obtain a porous ceramic sheet; S3: The prepolymer liquid is filled into the porous ceramic sheet in situ, cured under ultraviolet light, and then annealed to obtain the composite solid electrolyte. The prepolymer liquid includes macromonomers, vinyl monomers, lithium-ion polymerizable monomers, and photoinitiators.
2. The production method according to claim 1, characterized by, The macromonomers include polyethylene glycol diacrylate and / or polyethylene glycol dimethacrylate; The vinyl monomer includes any one or more of acrylamide, methyl methacrylate, or acrylonitrile; The lithium-ion-containing polymerizable monomers include lithium acrylate and / or lithium bis(fluorosulfonyl)imide; The photoinitiator includes any one or more of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, or diacylphosphine oxide; The prepolymer liquid contains, by mass, 4-6 parts of macromolecular monomer and 3-5 parts of vinyl monomer; The mass of the lithium-ion-containing polymerizable monomer is 10-20% of the total mass of the macromonomer and vinyl monomer; The mass of the photoinitiator is 1 to 3% of the total mass of the macromolecular monomer, vinyl monomer, and lithium-ion-containing polymerizable monomer.
3. The production method according to claim 1 or 2, characterized by, In the macroporous slurry, the mass of the NaCl whiskers is 30-40% of LATP; The NaCl whiskers have an aspect ratio of 5 to 10:1 and a diameter of 3 to 5 μm. The thickness of the macroporous slurry layer is 20~30 μm.
4. The production method according to any one of claims 1 to 3, characterized by, The lithium-containing material includes any one or more of lithium phosphate, lithium difluorooxalate borate, lithium difluorophosphate, or lithium nitride, and the particle size of the lithium-containing material is 0.2~0.5 μm; In the intermediate layer slurry, the mass of lithium-containing substances is 10-30% of LATP, and the mass of glucose is 20-30% of LATP; The glucose particles have a diameter of 1~2 μm; The thickness of the intermediate layer slurry is 15~20 μm.
5. The preparation method according to any one of claims 1 to 4, characterized in that, In the microporous slurry, the mass of nano-NaCl is 10-20% of LATP, and the mass of functional additives is 3-5% of LATP; The particle size of the nano-NaCl is 0.5~1 μm; The particle size of the functional additive is 0.2~0.5 μm; The thickness of the pore layer slurry is 10~15 μm.
6. The preparation method according to any one of claims 1 to 5, characterized in that, The pressurization pressure is 20~50MPa; The freeze-drying temperature is -20~-40℃, and the time is 24~48h; The pulse current has a current range of 10~30 kA and a frequency of 10 Hz~30 kHz.
7. The preparation method according to any one of claims 1 to 6, characterized in that, The porosity of the porous ceramic sheet is 45-55%.
8. The preparation method according to any one of claims 1 to 7, characterized in that, The parameters of the UV curing are: 365~385 nm, 500~800 mJ / cm 2 ; The annealing temperature is 130~150℃, and the time is 1~3 h; The thickness of the composite solid electrolyte is 50~80 μm.
9. The gradient pore composite solid electrolyte prepared by the preparation method according to any one of claims 1 to 8.
10. An all-solid-state battery, characterized in that, The gradient pore composite solid electrolyte prepared by the preparation method according to any one of claims 1 to 8.